Prenatal Cytogenetic Diagnosis in Cienfuegos: Years 2007-2018 - Pedro Alí Díaz-Véliz Jiménez; Belkis Vidal Hernández; Teresa Velázquez Martínez; Yoelkis Sanjurjo Pérez; Iliana González Santana (Revista Finlay)
Background: cytogenetic prenatal diagnosis is part of the care provided to the high-risk pregnant woman and is an indispensable component of preventive genetic programs promoted by the World Health Organization. Objective: to expose the results of the cytogenetic prenatal diagnosis in the Cienfuegos province between 2007 and 2018. Method: a descriptive, retrospective, statistical and chronological series analysis was carried out at the Provincial Center of Medical Genetics of Cienfuegos about all the cytogenetic prenatal diagnoses made between 2007 and 2018. There were analyzed: causes of study, number of diagnoses made, types of anomalies detected, relationship between causes of the study with the results of the diagnosis. Diagnoses were obtained from the database of the Institution's laboratory and a qualitative and quantitative assessment of their behavior was carried out during the period analyzed. The results are presented in tables using absolute numbers and percentages. Results: 3260 cytogenetic prenatal diagnoses were determined during the study period, 83 of them presented chromosomal alterations, for 2,6 % positivity. Only 33,7 % of positive cases and healthy carriers are under 37 years old. The most frequent chromosomal abnormality was the free trisomy of 21 (45,8 %), the structural aberrations were 21,7 %, the mosaics were 13,3 %, and the most frequent reason for indication among the positive cases was age advanced maternal (45 cases). Conclusions: the indicators analyzed behave similarly to those reported in 2012, in the literature of Cuba and the world.